Unveiling the Role of PHI in Prostate Cancer Diagnosis: Insights from an Indian Population Study - Gupta, Aman; Shukla, Vijay Kumar; Pankaj, Kumar; Chaudhari, Rajeev; Singh, Tarun; Gupta, Nidhi (Student’s Journal of Health Research Africa, 2024)
Introduction The Prostate Health Index (PHI) is based on various Prostate-specific Antigen (PSA) derivatives and has been approved in Europe, Australia, and the United States. PHI outperforms its components for the prediction of overall and high-grade prostate cancer on biopsy. This study aimed to evaluate the usefulness of the Prostate Health Index (PHI) in the Indian context and its role in guiding biopsy decisions when prostate-specific antigen (PSA) levels fall within the borderline or inconclusive range. Patients and Methods A total of seventy-five patients with PSA in the range of 4-20ng/ml were enrolled in the study. For each patient, PSA parameters including total PSA, free PSA, and p2PSA were determined from blood samples. PHI was determined using the formula (Beckman Coulter) PHI= (p2PSA/free PSA) x √ PSA. All the patients underwent Trans-rectal ultrasound (TRUS)-guided prostate biopsy. The diagnostic performances of these PSA derivatives were compared to predict carcinoma prostate. Results About 53.33% were found to be of benign etiology and 46.67% were of malignant etiology based on the histopathology report of the prostate biopsy. PHI had the highest Area UnderThe Curve (AUC) value of 0.9686, followed by p2PSA (0.9236). At the cut-off value of 35.7 PHI has a sensitivity of 94.28% and a specificity of 90% to detect high-grade malignancy. Using the cut-off value of PHI=35, 46.67% of the prostate biopsies could be prevented. Conclusion PHI outperformed PSA in detecting Prostate cancer (PC). Higher value of PHI was connected to high-grade PC. The authors strongly feel that PHI should be widely available in India. Recommendation Biopsy is recommended for patients receiving an intermediate to high-risk PHI score as opposed to biopsy patients receiving a low PHI score.